Legal Analysis Of The Failed Investment Of The Jakarta-Bandung High-Speed Rail Project: Ambition Vs Reality - Widi Nugrahaningsih; Seroja Kusuma Dewi; Rini Diah Puri Handayani (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The Jakarta–Bandung High-Speed Railway (KCJB) project, operated by PT Kereta Cepat Indonesia China (KCIC), represents Indonesia’s strong ambition to accelerate national strategic infrastructure development and strengthen bilateral cooperation with China. Nevertheless, behind its physical progress, the project has encountered serious challenges characterized by investment failure, including cost overruns, construction delays, and potential legal disputes. This article aims to analyze the failure of the KCJB investment from a legal perspective by examining the gap between infrastructure ambitions and Indonesia’s regulatory realities. This study employs a normative legal research method using statutory and conceptual approaches, supported by an extensive review of primary, secondary, and tertiary legal materials. The analysis reveals that the KCJB investment failure is largely driven by weak regulatory harmonization, legal uncertainty, imbalanced contract structures, and the complexity of financing schemes that were insufficiently anticipated within the existing legal framework. Furthermore, the absence of competitive tendering processes, overlapping authorities between central and regional governments, and limited legal protection for public interests have significantly increased investment risks. These conditions have ultimately undermined legal certainty and the effectiveness of project governance. The article concludes that strengthening regulatory frameworks, enhancing contractual transparency, and restructuring public–private partnership mechanisms are essential to mitigate the risk of investment failure in future large-scale infrastructure projects and to ensure that development ambitions align with the principles of legal certainty and good governance.